Development Strategy Of Micro, Small And Medium Enterprises Based On Creative Economy In Semolowaru Neighbourhood - Nugraheni Sri Lestari, Veronika; Toni, Ignasius; Nurmawati, Nurmawati; Cahyono, Dwi (Nomico, 2025)
The purpose of this study is to establish a plan for the growth of MSMEs in Semolowaru Village that is centered on the creative economy. This strategy is crucial for leveraging the expanding creative economy's potential to increase the competitiveness of regional MSMEs. Descriptive qualitative research methodology was employed, and data was gathered via document analysis, observation, and interviews. SWOT analysis was used to determine MSMEs' opportunities, threats, vulnerabilities, and strengths. The findings demonstrated that enhancing product quality, leveraging digital technology for marketing, growing networks of collaboration, and offering training to MSME participants are all ways to foster the growth of creative economy-based MSMEs in Semolowaru.  This research recommends collaboration between the government, business actors, and the community in building an ecosystem that supports the growth of creative economy-based MSMEs.